Draft Five Year Plan 1978-83 Rental Housing Government of Madhya Pradesh - Planning Commission (Planning Commission, 1978)
Draft Plan 1978-83, Head of Development-Outlays and Expenditure, States/UTs Heads-Outlays and Expenditure, Rental Housing Department, Selected Targets and Achievements.
Government of Madhya Pradesh, Planning, Economics and Statistics Department